Islamic Perspective on Marketing Strategy Through Quantitative Strategic Planning Matrix (QSPM) - Sulasih; Pramono Hari Adi; Weni Novandari; Suliyanto (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Although several papers have discussed Quantitative Strategic Planning Matrix (QSPM), there is still limited research that specifically discusses result marketing strategies for the results of QSPM in an Islamic perspective. The aim is to show that QSPM as an input for a marketing strategy is based on an Islamic perspective so that it becomes a grounded and conceptual theory by incorporating narrative verses from the Quran and Hadith. This research used a qualitative approach and is guided by the verses of the Quran and Hadith in supporting QSPM as an input for marketing strategies from an Islamic perspective. Findings from the QSPM, it is found that the alternative strategy that should be carried out is strategy 5, namely, by making unique batik patterns and motifs, it is hoped that the Batik Production business can increase the competitive advantage in the era of globalization and increasingly fierce competition with a Total Attractiveness Score (TAS) value of 6.22. The strategy of making unique patterns and motifs in an Islamic perspective is reflected in the Quran, Surah Ali-‘Imran verse 190 and Surah Ar-Ra’d verse 11